(untitled) (Global Journal of Science Frontier Research, 2023)
The main source of livelihood in Uganda is smallholder farming. It is the most common type of agriculture practice supporting more than 70% of the population, thus a dire need to devise means to sustain and improve it towards poverty reduction and socio-economic development resulting from the agricultural sector. This study investigates the Level and Suitability of ICT Usage for Agricultural Information Dissemination in Rubanda, Mayuge Districts, and Mbarara City of Uganda. The study adopted the survey design of the cross-sectional and used structured questionnaires. Data collected were analysed using descriptive statistics of frequency counts and percentages.